2014
DOI: 10.1007/s10461-014-0734-y
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Perceived Racial Discrimination in Black Men Who Have Sex with Men (MSM) and Its Association with Healthcare Utilization and HIV Testing

Abstract: In HPTN 061, a study of Black Men Who Have Sex with Men (MSM), we evaluated the association of healthcare-specific racial discrimination with healthcare utilization and HIV testing among 1167 HIV-negative participants. Median age was 38 years, 41% were uninsured, and 38% had an annual household income < $10,000. Overall, 19% reported healthcare-specific racial discrimination directed toward family, friend, or self; 61% saw a healthcare provider in the previous 6 months and 81% HIV tested within the past year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 32 publications
0
44
1
Order By: Relevance
“…Contrary to results from some studies, 30, 37, 38, 39 identifying as being black in our study was associated with higher frequency and rate of testing. This may be reflected of targeted testing campaigns to this high-risk group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to results from some studies, 30, 37, 38, 39 identifying as being black in our study was associated with higher frequency and rate of testing. This may be reflected of targeted testing campaigns to this high-risk group.…”
Section: Discussioncontrasting
confidence: 99%
“…37,38 White MSM may also experience less discrimination when interacting with healthcare providers, compared to black MSM, increasing their willingness to receive HIV testing through traditional healthcare services. 39 Therefore, black MSM may be a more suitable group to target for HIV testing outside of the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] A recent study of New York MSM found that although most had seen a clinical provider recently, 39 % did not disclose sexual activity with male partners, with lower rates among African American and Latino MSM. 15 Medical mistrust, [16][17][18][19] discrimination experiences, [18][19][20][21] conspiracy beliefs, 19,22,23 and concerns about disclosure may be particularly significant barriers to PrEP access among MSM of color, as demonstrated by a recent PrEP acceptability study among African American MSM. 24 Treatment mistrust and HIV conspiracy beliefs are also linked to sexual risk-taking and nonadherence to antiretroviral treatment 22,23 ; it is unknown how mistrust may now influence PrEP use.…”
mentioning
confidence: 99%
“…34 Despite acknowledgement of medical mistrust, perceived discrimination, and disclosure difficulties among MSWs and other MSM, little research has considered differences in how MSWs experience these phenomena. Many comparative analyses of medical mistrust and disclosure among subgroups of MSM focus on differences by race and ethnicity, [15][16][17][18][19][20][21][22][23][24]35 rather than sex work. Earnshaw and colleagues have proposed a comprehensive model linking mistrust to HIV risk, 35 which suggests that intersecting stigmas (e.g., based on race, sexual orientation, sex work, or incarceration) combine to influence disparities in risk, screening, treatment, and survival.…”
mentioning
confidence: 99%
“…For some MSM, personal experiences of stigma, discrimination, and homophobia regarding their sexual orientation can result in adverse mental health outcomes, including depression, anxiety, elevated stress, and suicidal thoughts and attempts (16)(17)(18)(19)(20)(21). Discrimination by health care providers (22), limited access to gay-friendly health services (23), and barriers to health insurance (23)(24)(25) also can contribute to HIV-related disparities experienced by MSM. The physical and mental health of MSM can be affected by syndemic conditions, which are conditions that individually or in combination can increase HIV risk.…”
Section: Adaptation and National Dissemination Of A Brief Evidence-bmentioning
confidence: 99%